IN SITU Raman analysis of electrochemical phenomena in carbon nanowalls - Zhumadilov Р.Е.; Nemkayeva Р.Р.; Yerlanuly Е.; Gabdullin М.Т. (Recent Contributions to Physics, 2024)
Carbon nanowalls (CNWs) are vertically oriented and interconnected graphene sheets. They are attracting growing interest as a new material for application in electrochemical sensing devices due to their high electrical and thermal conductivity, excellent electrocatalytic activity, large specific surface area and high sensitivity to various analytes. In this work, CNWs were synthesized on Ti2substrates by radical-injection plasma-enhanced chemical vapor deposition (RI-PECVD). The structural and morphological properties of the obtained CNWs were investigated by Raman spectroscopy and scanning electron microscopy. Cyclic voltammetry and chronoamperometry were used to analyze the electrochemical properties of the CNWs. The electrochemical properties of the CNWs were investigated in conjunction with in situ Raman spectroscopy. In situ Raman spectroscopy provides information on possible damage or disorder in the material and is an effective method to study phase transitions induced by temperature, pressure, or electrochemical reaction. The intentional applying of different values of voltages on the CNWs electrode allowed us to trigger electrochemical reactions, which we monitored with in situ Raman spectroscopy. The reactions were partially reversible, as indicated by the increase/decrease of the peak intensity ratio (I2D/IG).